Buddhist scriptures - Lopez, Donald S.,Jr. 1952- ([London] Penguin Group, 2004)
"This rich anthology brings together works ... from languages such as Pali, Sanskrit, Tibetan, Chinese and Japanese ..."
The Buddhist universe. The realms of rebirth ; A call to practise ; Karma tales ; A lesson from a ghost ; A scripture that protects kings ; One Buddha per universe ; Two Buddhas seated side by side ; Rebirth in the land of bliss ; Avoiding hell, gaining heaven ; A Chinese pilgrim in India ; A sacred peak ; Maitreya describes the future. -- The Buddha. The three jewels ; The noble search ; A life of the Buddha ; Māyā, mother of the Buddha ; Why the Buddha had good digestion ; A king gives away his head ; Rūpyāvatī gives away her breasts ; How the Buddha became a Bodhisattva ; Providing the Buddha ; Enshrining a relic ; The consecration of a Buddha image ; A hymn to the Buddha. -- Monastic life. The evolution of the ordination ; Making men into monks ; A murderer becomes a monk ; The ascetic ideal ; Monks in the Mahāyāna ; Making new monastic rules ; Lives of eminent monks and nuns ; The nine patriarchs of the East ; Taking the Vinaya across the sea ; Zen for national defence ; How a monk freed his mother from hell ; Living in the degenerate age.
"Penguin books."
"This rich anthology brings together works ... from languages such as Pali, Sanskrit, Tibetan, Chinese and Japanese"--Page 4 of cover.
Includes bibliographical references (pages [xlii]-xlix)
Keywords: Buddhist literature -- Translations into English; Buddhism -- Sacred books